Efficient Agrobacterium-mediated transformation and genome editing of Fagopyrum tataricum - Pinski, Artur; Betekhtin, Alexander (Frontiers in Plant Science, 2023)
Fagopyrum tataricum (L.) Gaertn. is an exceptional crop known for its remarkable health benefits, high levels of beneficial polyphenols and gluten-free properties, making it highly sought-after as a functional food. Its self-fertilisation capability and adaptability to challenging environments further contribute to its potential as a sustainable agricultural option. To harness its unique traits, genetic transformation in F. tataricum is crucial. In this study, we optimised the Agrobacterium-mediated transformation protocol for F. tataricum callus, resulting in a transformation rate of regenerated plants of approximately 20%. The protocol's effectiveness was confirmed through successful GUS staining, GFP expression, and the generation of albino plants via FtPDS gene inactivation. These results validate the feasibility of genetic manipulation and highlight the potential for trait enhancement in F. tataricum.